2009
DOI: 10.2174/1875398100902010009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Milk Oligosaccharides using Solid-Phase Extraction

Abstract: Abstract:A method was developed to isolate mono-and disaccharide-free oligosaccharides from human and bovine milk using a combination of enzymatic digestion of lactose and solid-phase extraction. In the initial trial, 2.5 g of oligosaccharides were isolated from one liter of human milk. In subsequent trials this was increased to over 5 g of oligosaccharides per liter. Compared to filtration-based extraction methods, this procedure allows for further isolation of oligosaccharide fractions via modulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 27 publications
2
57
0
Order By: Relevance
“…In the FCC and other future collider frameworks, the attendant precision physics programs necessitate IR-improved quantum field theory results to exploit properly the respective new physics windows. In quantum gravity, it has been found that resummed IR leads to UV finiteness [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. In what follows, we expand on these developments in IR-improvement of quantum field theory from the standpoint of applications to precision LHC/FCC physics and applications of one of us (BFLW) of quantum gravity.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the FCC and other future collider frameworks, the attendant precision physics programs necessitate IR-improved quantum field theory results to exploit properly the respective new physics windows. In quantum gravity, it has been found that resummed IR leads to UV finiteness [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. In what follows, we expand on these developments in IR-improvement of quantum field theory from the standpoint of applications to precision LHC/FCC physics and applications of one of us (BFLW) of quantum gravity.…”
Section: Introductionmentioning
confidence: 94%
“…One of us (BFLW) has shown [22,23,24,25] that the RQG realization of quantum gravity leads to Weinberg's [91] UV-fixed-point behavior for the dimensionless gravitational and cosmological constants and that the resummed theory is actually UV finite. He has shown further that the RQG theory, taken together with the Planck scale inflationary [92,93] cosmology formulation in Refs.…”
Section: Applications In Quantum Gravitymentioning
confidence: 99%
“…Intensive biochemical characterization of the carbohydrate molecules and their various bioactivities may facilitate an understanding of their importance in human nutrition and may suggest individual carbohydrate structures to target for industrial production [6]. Recently, many studies reveal the biological significance of some carbohydrates and their potential role as nutraceuticals.…”
Section: Need Of Fractionation Of Carbohydratesmentioning
confidence: 99%
“…The smallest OS, with a degree of polymerisation of 3, will often behave similarly to lactose when OS are enriched by polarity or size-based methods. Lactose can be hydrolysed enzymatically during sample preparation (Ninonuevo et al, 2007; Ward, 2009). The resulting monosaccharides are smaller and may be separated by size-exclusion approaches; however, it is often preferable to forgo this hydrolysis to avoid OS degradation and improve throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous publications have characterised the excellent retention characteristics of graphitized carbon in the context of glycan desalting and preconcentration (Packer, Lawson, Jardine, & Redmond, 1998; Redmond & Packer, 1999; Ward, 2009), the efficiency of the technique in separating milk OS and lactose has not been well-characterised, despite its widespread use for this purpose. Past chromatographic and extraction studies have shown that disaccharides, including lactose, can be substantially retained by graphitised carbon (Davies, Smith, Harbin, & Hounsell, 1992; Koizumi, Okada, & Fukuda, 1991; Redmond & Packer, 1999), indicating that extraction conditions would need to be carefully optimised for successful milk OS concentration by porous graphitized carbon (PGC) when lactose is present.…”
Section: Introductionmentioning
confidence: 99%